Factors Affecting People's Buying Interest in Boba Qiuqiunian Drinks - Preti Intan Sari; Muhammad Irwan Padli Nasution (Penerbit Jurnal Indonesia, 2022)
The purpose of this study is to find out what factors can influence people's buying interest in QIUQIUNIAN Boba drinks, in addition to knowing how to overcome competition between other competitors, as we know that now is the era of boba drinks, then to find out how QIUQIUNIAN Boba drinks introduce their products to be famous among the surrounding community, both children, teenagers and adults.